An exploratory study of motives for participation in extreme sports and physical activity. (1st January 2020) - Zhou, Lijun; Chlebosz, Karolina; Tower, John; Morris, Tony
Abstract: While participation in traditional sports and leisure-time physical activity (PA) is declining globally, participation in extreme sports is increasing. Few studies have examined the motives of participants in extreme sports. Adopting a qualitative design, we explored motives for participation in extreme sports in China. Participants were 14 adults who participated in extreme sports as serious leisure pursuits. We interviewed participants about the reasons they participated in their chosen activity. Each interview lasted between 40 and 60  minutes. We transcribed digital recordings verbatim and conducted an inductive-deductive content analysis. We identified 9 general dimensions (motives); 7 were consistent with participation motives in traditional sports (mastery, enjoyment, psychological condition, physical condition, affiliation, others' expectations, competition/ego), and 2 were new to extreme sports (vertigo, catharsis). We note limitations of this study, draw conclusions for future research, and propose implications for increasing participation in sport and PA arising from this study.